Rheological properties of SS316l MIM feedstock prepared with different particle sizes and powder loadings - M. Amin, Sri Yulis (The Institution Of Engineers, Malaysia, 2009)
Rheological study has been performed experimentally to evaluate the influence of different particle sizes and powder loadings to the rheological properties of SS316L MIM feedstock. The effects of different particle size, powder loading, shear rate and temperature has been investigated using capillary rheometer. The effect of shear rate to the feedstock viscosity was evaluated and result demonstrated that the feedstocks are pseudo-plastic. Their viscosity also shows strong dependence on the shear rate. The activation energy of each feedstock indicates the sensitivity to temperature and shear stress. The moldability index of the feedstock is also significant. The results indicate that the high powder loading feedstock at 64% volumes demonstrate the best rheological properties. The feedstock achieved desirable injection molding characteristics, such as homogeneous, stable, flow behavior index, n < 1, moderate activation energy (E) and high moldability index (a).